Dysregulation of iron metabolism in chronic kidney disease – hepcidin as a diagnostic biomarker in Iraqi adults – a case-control study - Tarweel, Mohammed Abdul Jaleel; Alammar, Haider Abd Jabber (Rzeszów University Press, 2026)
Introduction and aim. Chronic kidney disease (CKD) is a global health burden, with iron deficiency (ID) being a prevalent but under-diagnosed comorbidity. Traditional biomarkers, such as serum ferritin and transferrin saturation, are confounded by inflammation, which limits diagnostic accuracy. Hepcidin, a key regulator of iron homeostasis, offers potential as a reliable biomarker; however, data from low- and middle-income countries (LMICs), including Iraq, remain scarce. This study assessed the diagnostic utility of hepcidin for CKD and its association with iron dysregulation in Iraqi adults, addressing regional gaps in biomarker validation and clinical application. Material and methods. This case-control study (September 2024–February 2025) recruited 60 patients with CKD (stages 2–4) and 40 age-and sex-matched healthy controls. The exclusion criteria were recent transfusions, infections, or iron therapy. Serum hepcidin, ferritin, iron, Total Iron-Binding Capacity (TIBC), transferrin, and renal function indices were analyzed via enzyme-linked immunosorbent assay and standardized assays. Results. CKD patients exhibited significantly elevated hepcidin (39.8±23.1 vs. 13.7±4.8 pg/mL, p<0.001) and ferritin (246±128 vs. 160±61 ng/mL, p<0.001) but lower serum iron (12.38±3.1 vs. 118±33.5 μg/dL, p<0.001), TIBC (347±109 vs. 385±62 μg/dL, p=0.004), and transferrin levels (224±74 vs. 258±39 mg/dL, p=0.005) than controls. Hepcidin levels increased progressively with CKD stage (p<0.001) and correlated strongly with eGFR (r=-0.800, p<0.001) and serum creatinine (r=0.702, p<0.001). At a cut-off of >25 pg/mL, hepcidin demonstrated 80% sensitivity and 100% specificity for CKD diagnosis, with an AUC of 0.86 (95% CI: 0.78–0.92, p<0.001). Conclusion. Hepcidin demonstrated high diagnostic accuracy for CKD and was a superior indicator of iron metabolism dysregulation compared to traditional biomarkers. Its utility in resource-limited settings, such as Iraq, could enhance early CKD detection and guide management strategies, thereby addressing critical gaps in LMIC healthcare.
The study protocol, subject Information and approval form were reviewed and approved by the clinical chemistry unite of the laboratory in al Diwaniyah Teaching Hospital accordance with Document No. 472130 dated (29/10/2024) to obtain this approval.
Keywords: chronic kidney disease; diagnostic biomarker; hepcidin; iron deficiency